Understanding gesture: Is the listener’s motor system involved? - Ping, Raedy M. (2013)
Listeners are able to glean information from the gestures that speakers produce, seemingly without conscious awareness. However, little is known about the mechanisms that underlie this process. Research on human action understanding shows that perceiving another’s actions results in automatic activation of the motor system in the observer, which then affects the observer’s understanding of the actor’s goals. We ask here whether perceiving another’s gesture can similarly result in automatic activation of the motor system in the observer. In Experiment 1, we first establish a new procedure that uses listener response times to study how gesture impacts sentence comprehension. In Experiment 2, we use this procedure, in conjunction with a secondary motor task, to investigate whether the listener’s motor system is involved in this process. We show that moving arms and hands (but not legs and feet) interferes with the listener’s ability to use information conveyed in a speaker’s hand gestures. Our data thus suggest that understanding gesture relies, at least in part, on the listener’s own motor system.